The endogenic neurosteroid system and its role in the pathogenesis and therapy of mental disorders - Sakeena P. Bairamova; Dmitry S. Petelin; Roman V. Akhapkin; Nikita V. Kudryashov; Olga Yu. Sorokina; Sergey A. Semin; Veronika Panfilova; Beatrice A. Volel (Belgorod National Research University, 2023)
Introduction: Although neurosteroids have been relatively recently discovered, their significant role in the neurochemical processes and pathogenesis of a number of psychiatric and neurological disorders is now quite clear. First of all, it seems important to clarify the definition of the endogenous neurosteroids as a class of steroids, taking into account the variability of approaches to their description. Currently, neurosteroids include endogenous steroids synthesized in the central nervous system, gonads, or adrenal glands and interacting with GABAA, NMDA, and sigma-1 receptors. Neurosteroid biosynthesis: Biosynthesis of neurosteroids begins with rate-limiting reaction of TSPO binding cholesterol and transporting it into the mitochondria, where pregnenolone is synthesized following the cytochrome P450scc (CYP11A1) impact. Interaction with GABAА, NMDA and sigma-1 receptors: According to the experimental data, neurosteroids act as the most highly potent endogenous allosteric modulators of the GABA receptor; some types of neurosteroids (ALLO, DHEA, etc.) can produce a rapid anxiolytic and anticonvulsant effect. There is some experimental evidence for antipsychotic effects of some neurosteroids realized through NMDA receptors: intracerebral administration of ALLO to laboratory animals can prevent further appearance of motor agitation and other equivalents of psychosis after administration of high doses of amphetamines. It has also been proven in several studies on animal models that neurosteroids exhibit anxiolytic effects through sigma-1 receptors. Conclusion: The article describes the process of neurosteroidogenesis and the effect of neurosteroids on listed receptorsin accordance with already available scientific data. In addition, this paper describes the specific role of various neurosteroids in the development of mental illnesses, including anxiety disorders, depression, and schizophrenia.